A Multifunction Robot Based on the Slider-Crank Mechanism: Dynamics and Optimal Configuration for Energy Harvesting - Arnaud Notué Kadjie; E. B. Tchawou Tchuisseu (International Journal of Robotics and Control Systems, 2021)
An electromechanical robot based on the modified slider-crank mechanism with a damped spring hung at its plate terminal is investigated. The robot is first used for actuation operation and for energy harvesting purposes thereafter. Mathematical modeling in both cases is proposed. As an actuator, the robot is powered with a DC motor, and the effect of the voltage supply on the whole system dynamics is found out. From the numerical simulation based on the fourth-order Runge-Kutta algorithm, results show various dynamics of the subsystems, including periodicity, multi-periodicity, and chaos as depicted by the bifurcation diagrams. Applications can be found in industrial processes like sieving, shaking, cutting, pushing, crushing, or grinding. Regarding the case of the robot functioning as an energy harvester, two different configurations of the electrical circuit for both single and double loops are set up. The challenge is to determine the best configuration for the high performance of the harvester. It comes from theoretical predictions and experimental data that the efficiency of the robot depends on the range values of the electrical load resistance RL. The double loop circuit is preferable for the low values of RL50 Ohm) while the single loop is convenient for high values of RL ≥ 50 Ohm.